The newspaper designer's handbook - Harrower, Tim (McGraw-Hill, 2002)
The Newspaper Designer’s Handbook is a step by step guide to every aspect of newspaper design, from basic page layout to complex infographics. The new edition is now in 4-color and introduces a new chapter on web design. This textbook is for journalism students and professionals alike. It is loaded with examples, advice, design ideas, and exercises that teach students how to manipulate the basic elements of design (photos, headlines, and text); create charts, maps, and diagrams; design attractive photo spreads; add effective, appealing sidebars to complex stories; create lively, engaging feature page designs; work with color; and redesign a newspaper.